A Prophylactic Effect of PNF Stretching on Mechanical Parameters of Deep Jump following Exercise-Induced Muscle Damage - Ali Jalalvand; Mehrdad Anbarian (Allameh Tabataba'i University Press, 2020)
Purpose: Prophylactic effect of PNF stretching is performed with an expectation to reduce the risk of eccentric exercise-induced muscle damage and enhance drop jump performance.The purpose of this study was to examine the effects of proprioceptive neuromuscular facilitation stretching combined with plyometric training on deep jump in non-athlete male students. Method: The study design was a single blinded, randomized, concurrent parallel trial. Forty-two non-athlete male students were volunteered to participate in this study. Participants were assigned into plyometric (n=21) and plyometric & PNF (n=21) groups. Maximum and minimum vertical displacements, flight time, joint power, maximum landing force, peak take off instantaneous velocity were measured at baseline and 48 hours following the plyometric exercise protocol. A Vicon (200 Hz) motion analysis system with six T-Series cameras and two Kistler force plates (1000 HZ) were used to record kinematic and kinetic data, respectively. A two-way repeatedmeasure ANOVA (group x DOMS) was used to analyze data. Results: There was a significant difference between the pretest and the posttest scores in the intervention group for maximum vertical displacement (p=0.028), flight time (p=0.042), and Power average (p=0.026). Conclusions: This prophylactic treatment on mechanical parameters of deep jump during timing was useful. Eventually, results suggest that preventative treatments can have a significant effect on maintenance functional parameters or even helping to slow exercise-induced muscle damage for alleviating its symptoms.